Decreased physical activity is a predictor for a complicated recovery post cardiac surgery - van Laar, Charlotte (Health Qual Life Outcomes, 2017)
BACKGROUND: Physical activity (PA) reduces the risk of cardiovascular disease and physically active survivors of a cardiac event are at lower risk of recurrent events. We hypothesized that patients with a decreased PA, undergoing cardiac surgery, are at higher risk for a postoperative complicated recovery (PCR). METHODS: Three thousand three hundred eighty two patients undergoing elective cardiac surgery between January 2007 and December 2013 were included. The group was divided into three subgroups: group A, aged ≤ 65 years (N = 1329); group B, aged > 65 years and ≤ 75 years (N = 1250); and group C aged >75 years (N = 803). To assess PA, the criteria of the Corpus Christy Heart Project were used. A PCR consists of the occurrence of a major postoperative event, defined as any of the following complications: reoperation, deep sternal wound infection, renal failure, stroke, postoperative ventilation > 2 days, intensive care stay ≥ 5 days, hospital stay ≥ 10 days, or hospital mortality. RESULTS: One thousand three hundred sixty seven patients (40%) were considered as patients with a decreased PA. Both in group B (p = 0.001) and in group C (p = 0.003), patients with a decreased PA were significantly associated with an increased risk of a PCR, which was not the case in group A (p = 0.28). Logistic regression analysis identified a decreased PA as an independent predictor for PCR in groups B (p = 0.003, odds 1.71) and C (p = 0.033, odds 1.48), but not in group A (p = 0.11, odds 0.71). CONCLUSION: Decreased physical activity is an independent predictor for a PCR in patients aged 65 years or older undergoing elective cardiac surgery.